Modification of Magnetite Nanoparticles with Triazine-Based Dendrons and Their Application as Drug-Transporting Systems - Mateusz Pawlaczyk (MDPI AG, 2021)
The following research aims at the synthesis of magnetite nanoparticles functionalized with triazine-based dendrons and the application of the obtained materials as effective sorptive materials dedicated to acidic bioactive compounds. The adopted synthetic approach involved: (1) the synthesis of nanosized Fe3O4 particles via classic co-precipitation method, (2) the introduction of amine groups on their surface leading to materials’ precursor, and (3) the final synthesis of branched triazine-based dendrons on the support surface by an iterative reaction between cyanuric chloride (CC) and piperazine (p) or diethylenetriamine (DETA) via nucleophilic substitution. The characterized materials were tested for their adsorptive properties towards folic acid, 18β–glycyrrhetinic acid, and vancomycin, showing high adsorption capacities varying in the ranges of 53.33–401.61, 75.82–223.71, and 68.17–132.45 mg g−1, respectively. The formed material–drug complexes were also characterized for the drug-delivery potential, performed as in vitro release studies at pH 2.0 and 7.4, which mimics the physiological conditions. The release profiles showed that the proposed materials are able to deliver up to 95.2% of the drugs within 48 h, which makes them efficient candidates for further biomedical applications.